Mining companies and sustainability: role of CSR in Canadian mining companies in Brazil - Kazantseva, Mariia (2020)
Given the rising interest in corporate social responsibility and tighter scrutiny in environmental regulation compliance, mineral extraction companies have encountered more challenges in their internationalization process. Despite extended research on CSR in developed countries, little attention has been paid to sustainability issues in emerging market economies. This document presents internationalization barriers mining firms from developed countries face in Latin America. This is illustrated by the analysis of two Canadian mining companies' (Kinross and Belo Sun) efforts to gain legitimacy around their golden mining operations in Brazil for further expansion. The work maps the literature systematically, assesses the embeddedness of CSR in business, discusses main empirical features, summarizes key findings and identifies best practices. The research finds that better environmental performance leads to overall cost reduction in the long term and can be associated with a better performance of the firm. The comprehensive review provided in the work also helps to understand CSR implementation practice in emerging countries and offers new frameworks that can set an agenda for future expansion strategies of foreign-owned companies in Latin America.